Funding for coronavirus health worker payments - I. Yu. Bocharova; A. Yu. Rymanov (IRBIS LLC, 2022)
Objective: to conduct an analysis of the channels, the volume of COVID payments to medical workers and assess the preliminary effectiveness of funding for coronavirus health worker payments.Material and methods. Statistical comparative analysis of data in the field of health care funding was carried out. The assessment of changes in the level of wages of medical workers was performed using the index method and the grouping method. Relative indicators of the structure were used to evaluate the distribution of transfers by region. The study was conducted on the basis of open Rosstat data on the salaries of medical workers.Results. The regional distribution of transfers was regulated in 2020 by the Federal Government. The main channel for financing COVID payments to medical workers was the allocation of transfers and subsidies. More than half of the funding was accounted for by transfers for incentive payments to health care workers for fulfilling particularly important works. The largest share of allocated transfers fell on the Moscow Region (5.6% of the total volume of transfers), Nizhny Novgorod Region (5.1%), and Saint Petersburg (5.0%), the lowest - on the Republic of Kalmykia, the Republic of Khakassia, the Amur Region (0.2% each), the Nenets Autonomous District (0.1%). Transfers for incentive payments for special working conditions and additional workload were paid in 2020 in a total of 670 thousand persons. Transfers for incentive payments for fulfilling particularly important works were paid in a total of 363 thousand medical workers and 53 thousand ambulance drivers. An assessment of the effectiveness of financing COVID payments in the form of transfers and subsidies showed that it was largely due to them that the medical workers' mean salary increased.Conclusion. The distribution of aggregated amounts of transfers between the constituent entities of the Russian Federation was carried out until November 2020 on the basis of the number of persons insured under Compulsory Health Insurance program in a corresponding region. In the early months of fighting the pandemic, the use of this aggregate was appropriate.